2005
DOI: 10.3184/030823405774662995
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the oxidation ability of protected hydrazine derivatives

Abstract: In the present paper we have determined the oxidation potentials for several protected hydrazine derivatives using cyclic voltammetry. For comparison the chemical oxidation of these hydrazines was also studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Generally, the oxidation of hydrazine is dependent on the reaction media; therefore, coulometric n values of 1, 2, and 4 have been reported for dimethylsulfoxide, acetonitrile , and aqueous solvents, respectively. Furthermore, Michlmayr and Sawyer demonstrated that the reaction of 1,1‐ and 1,2‐dimethylhydrazine undergoes a four‐electron process in dimethylsulfoxide containing 20 % water, which emphasizes the importance of water in the complete oxidation of hydrazine . Representative current blips are given in Figure for the oxidation of DPH in a toluene droplet.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the oxidation of hydrazine is dependent on the reaction media; therefore, coulometric n values of 1, 2, and 4 have been reported for dimethylsulfoxide, acetonitrile , and aqueous solvents, respectively. Furthermore, Michlmayr and Sawyer demonstrated that the reaction of 1,1‐ and 1,2‐dimethylhydrazine undergoes a four‐electron process in dimethylsulfoxide containing 20 % water, which emphasizes the importance of water in the complete oxidation of hydrazine . Representative current blips are given in Figure for the oxidation of DPH in a toluene droplet.…”
Section: Resultsmentioning
confidence: 99%
“…Our original idea to regenerate azodicarboxylates 1 from the corresponding hydrazides 2 led us to flavin photocatalysts. 15,16 Upon excitation with blue light (450 nm), flavins become oxidizing agents 17 (E * red ¼ 1:67 V vs: SCE for riboflavin tetraacetate (3b)), strong enough to oxidize 2 (a value of E * ox ¼ 1:62 V vs: SCE has been reported for BocNHNHBoc 18 ), but not so strong as to mediate undesired oxidation of alcohols, even when they are activated, e.g. benzyl alcohols, which are often substrates of Mitsunobu reactions.…”
mentioning
confidence: 99%
“…Recently, we, and other groups, have developed several reaction systems to carry out aerobic oxidations of disubstituted hydrazines [11,12] . Notably, our developed CuI/DMAP system was effective for the oxidation of hydrazinedicarboxylates, which have high oxidation potentials [11a,13] . Building from our previous work, and inspired by the reports described above, we envisioned that the aerobic oxidative azo‐ene cyclization of hydrazinedicarboxylates containing an ene moiety might be possible.…”
Section: Methodsmentioning
confidence: 96%